The pharmacokinetic study on the interaction between nobiletin and anemarsaponin BII in vivo and in vitro - Jie Zhang; Meiling Fan; Xia Yu; Bin Zhang (Taylor & Francis Group, 2021)
Context The interaction between nobiletin and anemarsaponin BII could affect the pharmacological activity of these two drugs during their combination. Objective The co-administration of nobiletin and anemarsaponin BII was investigated to explore the interaction and the potential mechanism. Materials and methods Male Sprague-Dawley rats were only orally administrated with 50 mg/kg nobiletin as the control and another six rats were pre-treated with 100 mg/kg anemarsaponin BII for 7 d followed by the administration of nobiletin. The transport and metabolic stability of nobiletin were evaluated in vitro, and the effect of anemarsaponin BII on the activity of CYP3A4 was also assessed to explore the potential mechanism underlying the interaction. Results The increasing Cmax (2309.67 ± 68.06 μg/L vs. 1767.67 ± 68.86 μg/L), AUC (28.84 ± 1.34 mg/L × h vs. 19.57 ± 2.76 mg/L × h), prolonged t1/2 (9.80 ± 2.33 h vs. 6.24 ± 1.53 h), and decreased clearance rate (1.46 ± 0.26 vs. 2.42 ± 0.40) of nobilein was observed in rats. Anemarsaponin BII significantly enhanced the metabolic stability of nobiletin in rat liver microsomes (half-life increased from 31.56 min to 39.44 min) and suppressed the transport of nobiletin in Caco-2 cells (efflux rate decreased from 1.57 ± 0.04 to 1.30 ± 0.03). The inhibitory effect of anemarsaponin BII on CYP3A4 was also found with an IC50 value of 10.23 μM. Discussion and conclusions The interaction between anemarsaponin BII and nobiletin was induced by the inhibition of CYP3A4, which should draw special attention in their clinical co-administration.